2017
DOI: 10.1371/journal.pone.0189109
|View full text |Cite|
|
Sign up to set email alerts
|

The role of cortical oscillations in a spiking neural network model of the basal ganglia

Abstract: Although brain oscillations involving the basal ganglia (BG) have been the target of extensive research, the main focus lies disproportionally on oscillations generated within the BG circuit rather than other sources, such as cortical areas. We remedy this here by investigating the influence of various cortical frequency bands on the intrinsic effective connectivity of the BG, as well as the role of the latter in regulating cortical behaviour. To do this, we construct a detailed neural model of the complete BG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(112 citation statements)
references
References 161 publications
(263 reference statements)
1
111
0
Order By: Relevance
“…Evidence suggests that oscillations in some 34 certain bands in the striatum and the subthalamic nucleus (STN), the input structures 35 of the BG, are driven by cortical regions [22][23][24][25]. Taking this into account, in previous 36 work [26] we explored the impact of cortical rhythmic activity on the BG function and 37 we found that the former can completely shape which areas of the BG circuit are active. 38 Yet, the connection between the BG, cortical oscillations and decision making still 39 remains relatively unexplored.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Evidence suggests that oscillations in some 34 certain bands in the striatum and the subthalamic nucleus (STN), the input structures 35 of the BG, are driven by cortical regions [22][23][24][25]. Taking this into account, in previous 36 work [26] we explored the impact of cortical rhythmic activity on the BG function and 37 we found that the former can completely shape which areas of the BG circuit are active. 38 Yet, the connection between the BG, cortical oscillations and decision making still 39 remains relatively unexplored.…”
mentioning
confidence: 95%
“…To achieve 42 this, we initially defined a number of metrics that enable the assessment of the 43 effectiveness of possible selection mechanisms. Using the biologically plausible neural 44 model of the BG circuitry defined in [26], we then carried out an analysis of the 45 relationship between cortical frequencies, dopamine concentration and BG selectivity. 46 We found that the frequency and phase difference between oscillatory cortical areas, 47 the level of dopamine in the system and the examined time scale, all have a very sequentially perform selection tasks, the strongly-active cortical areas instruct the mode 53 of this selection via their oscillatory activity.…”
mentioning
confidence: 99%
See 3 more Smart Citations